A strategy for enhancing ceramic densification in ultra-low temperature sintering: Shape-tailored nanostructure for crystal synthesis. Issue 8 (15th April 2023) - Wang, Xiaofei; Li, Jinping; Yang, Cheng; Zhang, Hui; Meng, Songhe
Abstract: It is difficult to achieve densification for metastable ceramics at ultra-low temperatures sintering due to insufficient sintering kinetics. Here, one strategy is proposed to enhance ceramic densification based on the principles of grain refinement and interface modification, in conjunction with a cold sintering process (CSP, 190 °C, 1 − 240 min, and 350 MPa) to achieve ceramic fabrication in a solid-liquid coexistence sintering environment. ZrW2 O8 @ZrO2 metastable composites as an example to demonstrate the effect of surfactant on grain tailoring and interfacial structure design during the hydrothermal assembly. The results show that the densities and mechanical strengths of the composite ceramics were significantly improved after the shape tailoring. Furthermore, the shape-tailored strawberry-like nanostructure enables the ZrW2 O8 to be split into smaller individual units, which allows the composites to achieve a high-level of zero thermal expansion ( α ‾ = 0.045 × 10 −6 °C −1 [-10 − 300 °C]). Such a methodology can effectively solve ceramic densification in ultra-low temperature sintering and provide a practical path for the fabrication of metastable ceramics.